Challenging Parenting Behavior from Infancy to Toddlerhood: Etiology, Measurement, and Differences between Fathers and Mothers. (30th November 2015) - Majdandžić, Mirjana; de Vente, Wieke; Bögels, Susan M.
Abstract : Based on evidence that fathers show more challenging and physical play than mothers, it has been theorized that fathers have a different parenting role, more focused at stimulating exploration and taking chances. Challenging parenting behavior (CPB) may foster confidence and buffer against anxiety development in children. In this study, CPB was assessed in fathers and mothers at child ages of 4 months, 1 year, and 2.5 years, using newly developed questionnaires and observational tasks. Reliability of the questionnaire and observational measures was good, and fathers' and mothers' self‐rated CPB showed a similar factor structure. Modest and significant convergence between questionnaires and observations provided support for validity of CPB, whereas negative correlations with overprotection supported divergent validity. CPB correlated positively with warmth. We further found moderate to high stability of CPB from early infancy to toddlerhood, and interparental correspondence in CPB. Fathers and mothers did not differ in observed CPB, but fathers rated themselves higher than mothers in toddlerhood. It is concluded that the development of the instruments to assess CPB was successful. Overall, the results reveal similarities rather than differences between fathers' and mothers' CPB in early childhood. The potential relevance of CPB in child development and psychopathology is discussed.